Highly efficient and selective photocatalytic CO2 reduction using MIL-125(Ti) and based on LiFePO4 and CuO QDs surface–interface regulation. Issue 16 (11th July 2022) - Zhou, Jun; Jia, Qinwei; Wang, Luyu; Zhao, Yuhang; Ma, Xiaofan; Gong, Lei; Zhang, Haonan; Zuo, Tong
Abstract : In this study, CuO quantum dots were encapsulated in a MIL-125(Ti) MOF via a simple oxidation method. Abstract : In this study, CuO quantum dots were encapsulated in a MIL-125(Ti) MOF via a simple oxidation method. Upon loading of LiFePO4 the composite material LiFePO4 /CuO@MIL-125(Ti) was formed. Due to the protection of the MIL-125(Ti) MOF, the composite photocatalyst exhibited stability in water. LiFePO4 provided transferable electrons to the CuO QDs which significantly improved the efficiency and selectivity of the photocatalytic CO2 reduction. Experiments showed that, at an optimal ratio of 2.5% LiFePO4 /1.0% CuO@MIL-125(Ti), the photocatalyst had its highest photocatalytic reduction activity for CO2 conversion in the presence of water. The optimized photocatalyst gave yields of methanol, ethanol, and acetic acid of up to 445.38, 966.36, and 844.63 μmol g −1, respectively. This work delivered a robust route for embedding CuO QDs and lithium battery materials into the surface matrix of photocatalysts for the effective reduction of CO2 .